Development of mobile robot and localization system - Juhari, Khairul Anuar (2014)
Mobile robot is currently being actively developed for both civilian and military use to perform dull, dirty and dangerous activities. Mobile robot is autonomous in nature, capable of operating over a wide variety of terrain and can be characterized by different speed, sensor range and weapons capabilities. Thus, the research involves designing an indoor mobile robot and creating algorithm for the mobile robot to localize. As such, the purpose of this thesis is to develop the localization of the mobile robot based on Extended Kalman Filter (EKF) method. The process begins with the mobile robot mechanical design where a selection of wheel types and types of locomotion are selected. Then the odometry corrections using a method called University of Massachusetts Benchmark (UMBmark ) method has been used to improve the encoder readings. As a part of the research contribution, a Circular Bencmark (CBmark) method is created in order to improve the motor speed by calibrating the encoder speed readings on each motor. Then the algorithm is built based on EKF method and tested via simulations. The simulation runs on two different cases that require the mobile robot to move to the target location while the time to accomplish and the distance between the mobile robot center gravity (cog) are taken. Then, the same algorithms are put on the hardware and the experiment runs same as in simulations. The performance of the mobile robot is compared between simulations and the real experiment based on graph of performance.